Towards wireless highly sensitive capacitive strain sensors based on gold colloidal nanoparticles. Issue 22 (25th May 2018) - Nesser, H.; Grisolia, J.; Alnasser, T.; Viallet, B.; Ressier, L.
Abstract : Highly sensitive capacitive strain sensors based on colloidal gold nanoparticles are designed, produced and characterized in order to address wireless applications. Abstract : We designed, produced and characterized new capacitive strain sensors based on colloidal gold nanoparticles. The active area of these sensors, made up of a 1 mm 2 close-packed assembly of gold nanoparticles between interdigitated electrodes, was designed to achieve measurable capacitance (>∼1 pF) and overcome parasitic capacitances. Electro-mechanical experiments revealed that the sensitivity of such capacitive sensors increases in relation to the size of the nanoparticles. In the case of 14 nm gold NPs, such sensors present a relative capacitance variation of −5.2% for a strain of 1.5%, which is more than 5 times higher than that observed for conventional capacitive strain gauges. The existence of two domains (pure capacitive domain and mixed capacitive–resistance domain) as a function of the frequency measurement allows for the adaptation of sensitivity of these capacitive sensors. A simple low-cost circuit based on a microcontroller board was finally developed to detect the capacitance variations of such NP based strain sensors. This low-cost equipment paves the way for the development of an entirely wireless application set-up.